2018
DOI: 10.14303/jribm.2018.018
|View full text |Cite
|
Sign up to set email alerts
|

Capital structure and financial performance of listed manufacturing firms in Nigeria

Abstract: This study examined the impact of capital structure on financial performance of quoted manufacturing firms in Nigeria over the period 2005-2014. Panel methodology was applied to analyse the impact of capital structure on financial performance of quoted manufacturing firms in Nigeria. The findings of the panel ordinary least square show that a positive statistically significant relationship exist between long term debt ratio(LTD) (0.0001), total debt ratio (TD) (0.0065) and return on equity (ROE) while a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 5 publications
4
13
0
Order By: Relevance
“…This reflects that increase in a unit increase in liquidity risk will lead to about 3.20billion increase in profit after tax as measure of performance. The study was in agreement with the conclusion of Ajibola et al (2018). Most of these firms have access to more current asset relative to current liabilities which make them avoid the risk of insolvency and encourage operational efficiency.…”
Section: Data Analysis and Discussion Of Findingssupporting
confidence: 86%
See 2 more Smart Citations
“…This reflects that increase in a unit increase in liquidity risk will lead to about 3.20billion increase in profit after tax as measure of performance. The study was in agreement with the conclusion of Ajibola et al (2018). Most of these firms have access to more current asset relative to current liabilities which make them avoid the risk of insolvency and encourage operational efficiency.…”
Section: Data Analysis and Discussion Of Findingssupporting
confidence: 86%
“…Therefore, study concluded that firms that take on enterprise risk management achieve more than firms that have not taken it on. Ajibola et al (2018) examined risk management and financial performance of deposit money banks in Nigeria. The study specifically investigated the impact of risk management (credit and liquidity) on financial performance of money deposit banks in Nigeria.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is supported by trade-off theory which stated indicated the highly profitable firms will have higher debt levels to maximize taxation benefits and increase the available of capital. The expected positive sign of TDTA have the same outcome as the prior studies such as Ajibola, Wisdom and Qudus (2018) who studied on manufacturing firms in Nigeria from 2005 to 2014 and they concluded that a positive significant relationship exists between TDTA and ROE. Besides, this outcome is consistent with the research of Ganiyu, Adelopo, Rodionova and Samuel (2019) which mentioned that TDTA has positive and significant effect on ROE in the sample of non-financial firms in Nigeria from 1998 to 2015.…”
Section: Effect Of Capital Structure On Roesupporting
confidence: 75%
“…They used 115 listed non-financial firms in Nigeria from 2005 to 2014. Meanwhile, Ajibola, Wisdom and Qudus (2018) discovered that from the results of the panel ordinary least square (OLS), LTDTA and TDTA have positive and significant impact on ROE while STDTA has a positive and insignificant on ROE. Besides, there was an insignificant and negative relationship between LTD, STD and TD and ROA.…”
Section: Empirical Evidencementioning
confidence: 99%